2021
DOI: 10.1093/brain/awab255
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic derangements are associated with impaired glucose delivery following traumatic brain injury

Abstract: Metabolic derangements following traumatic brain injury are poorly characterised. In this single-centre observational cohort study we combined 18F-FDG and multi-tracer oxygen-15 PET to comprehensively characterise the extent and spatial pattern of metabolic derangements. Twenty-six patients requiring sedation and ventilation with intracranial pressure monitoring following head injury within a Neurosciences Critical Care Unit, and 47 healthy volunteers were recruited. Eighteen volunteers were excluded for age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 57 publications
0
29
0
Order By: Relevance
“…1b) and recent combined multitracer oxygen-15 and 18 F-FDG PET studies confirm evidence of ischemic CBF reductions in acute TBI on the basis of a critical increase in both OEF and glycolysis (k 3 ) (Fig. 2) [5 ▪▪ ]. The authors demonstrated that the ischemic brain volume (IBV) within the first 24 h following injury was associated with worse outcome using the Glasgow Outcome Score.…”
Section: Defining Derangements In Cerebral Metabolism Following Traum...mentioning
confidence: 68%
See 1 more Smart Citation
“…1b) and recent combined multitracer oxygen-15 and 18 F-FDG PET studies confirm evidence of ischemic CBF reductions in acute TBI on the basis of a critical increase in both OEF and glycolysis (k 3 ) (Fig. 2) [5 ▪▪ ]. The authors demonstrated that the ischemic brain volume (IBV) within the first 24 h following injury was associated with worse outcome using the Glasgow Outcome Score.…”
Section: Defining Derangements In Cerebral Metabolism Following Traum...mentioning
confidence: 68%
“…In fact, bedside clinical monitoring of brain tissue oxygen and cerebral metabolism using microdialysis demonstrate evidence of persistent metabolic derangements which correlate with patient outcome [ 3 ▪▪ ]. Imaging studies using 15 oxygen PET demonstrate reductions in cerebral blood flow (CBF) and increases in oxygen extraction fraction (OEF) which are consistent with ischemia, but this finding is less common beyond the first 24 h after injury [ 4 ▪▪ , 5 ▪▪ ]. At these later time points following TBI, metabolic derangements are more consistent with disruption of the microcirculation resulting in tissue hypoxia or low brain glucose delivery, and/or mitochondrial dysfunction [ 5 ▪▪ ].…”
Section: Introductionmentioning
confidence: 99%
“…The ability to address ischemic hypoxia due to inadequate CBF, and prevent hyperemia, may be enhanced by using bedside techniques that assess in real time the status of cerebrovascular pressure reactivity, and to determine patient-specific optimal CPP ( 19 , 20 ). Flow dependency is not only an issue for oxygen but also for glucose delivery; neuroglycopenia can be an independent cause for energy crisis ( 21 ). Recent studies employing multimodality imaging and invasive tissue monitoring suggest that flow-dependent cerebral energy crisis—that is, ischemia due to low CPP/CBF—is not the sole and may not be the dominant SBI mechanism beyond the resuscitative phase ( 21 23 ).…”
Section: Flow-dependentmentioning
confidence: 99%
“…Flow dependency is not only an issue for oxygen but also for glucose delivery; neuroglycopenia can be an independent cause for energy crisis (21). Recent studies employing multimodality imaging and invasive tissue monitoring suggest that flow-dependent cerebral energy crisis-that is, ischemia due to low CPP/CBF-is not the sole and may not be the dominant SBI mechanism beyond the resuscitative phase (21)(22)(23).…”
Section: Flow-dependentmentioning
confidence: 99%
“…However, characterizing glucose metabolism is often limited to measuring the cerebral metabolic rate of glucose (CMRGlu), due to the challenges associated with obtaining microparameters at a voxelwise level [4]. A growing interest in understanding how CMRGlu is potentially affected by disease-related alterations in glucose delivery and phosphorylation [5,6] fosters further investigations.…”
Section: Introductionmentioning
confidence: 99%